PERANAN KELOMPOK KAYOMAN PEDAWA DALAM MEREVITALISASI POTENSI WISATA BERBASIS KEARIFAN LOKAL DI DESA PEDAWA, KECAMATAN BANJAR, KABUPATEN BULELENG - Putu Sabda Jayendra; I Wayan Eka Sudarmawan; Firlie Lanovia Amir (Jurnal Ilmiah Hospitality Management, 2019)
Kayoman Pedawa Group, directly initiated by the community of Pedawa Village aims to reconstruct and revitalize the existence of tourism potential in the form of natural, social, customs and local wisdom. The establishment of this group originated from the concerns of the community and the young figures Pedawa village will be the phenomenon of the growing nature and local wisdom with the rapid modernization. Therefore, the interest is examined from the phenomenon is and the role of the group Kayoman Pedawa in revitalizing the potential tourism-based local wisdom of Pedawa village. The theory used as a problem surgeon is the social action theory and structural functionalism theory. This research is a type of qualitative descriptive research. The results of the research is a revitalizing cultural potential based on local wisdom by Kayoman Pedawa Group of some of them are; 1) rehabilitation of forests and agricultural cultures, 2) revitalization of ancient relics into tourism destinations of village history, 3) The reconstruction of local wisdom-based attractions, such as traditional houses, gangsing games, traditional gamelan reconstruction of Pedawa , revitalizing the manufacture and product of palm sugar Pedawa, 4) provide a mentoring of foreign students who study ethnography, and 5) socialization and publication of local wisdom of Pedawa village to the outside community, such as the interactive dialogue of Thunder Singaraja Radio broadcast, Through the making of documentary films in collaboration with Minikino Bali.